ASEAN's Free Trade Agreements with the People's Republic of China, Japan, and the Republic of Korea: A Qualitative and Quantitative Analysis - Gemma Estrada; Donghyun Park; Innwon Park; Soonchan Park (Asian Development Bank (ADB), 2011)
Expanding trade with East Asia's "Big Three" economic giants—the People's Republic of China (PRC), Japan, and the Republic of Korea—offers a new potential source of growth for ASEAN in the post-global-crisis period. In fact, ASEAN has been actively pursuing trade liberalization with the Big Three. The central objective of this paper is to qualitatively and quantitatively assess the different permutations of ASEAN's free trade agreements (FTAs) with the Big Three (e.g., ASEAN–PRC, ASEAN–Japan, ASEAN–Republic of Korea, and ASEAN+3). Our qualitative analysis is based on the theory of economic integration, and our quantitative analysis is based on a CGE model. The two types of analyses both suggest that an ASEAN+3 FTA would deliver the largest benefits for the region.
hdl:11540/2037
Keywords: F10; F14; F15; 330; ASEAN; People's Republic of China (PRC); Japan; Republic of Korea; trade; free trade agreement; free trade area; CGE model